The Evolution of Norms in Trade and Financial Networks in the First Global Age: the case of Simon Ruiz's network - Ribeiro, Ana Sofia (2017)
In the 16th century, merchants and bankers gained a social influence and political relevance, due to their capacity of ‘faire travailler l’argent des autres’ (Benassar 1972:50). For the success of their activity, they built evolving networks with cooperative partners. These networks were much more than the sum of all partners. In the case study of the Castilian merchant Simon Ruiz, the network functioned in an unique way and independent from any formal institutional control. Its functioning varied in how different partners were associated and the particular characteristics and contents of these social ties. Being a self-organized network, since the formal institutions of trade regulation and the Crown control didn’t influence the network functioning, the Simon Ruiz network was deeply embedded in the economic and financial performance of the Hispanic Empires, in two different ways. The first, purely commercial. The monopolistic regime which was applied by the two crowns in the trade of certain colonial goods was insufficient to the costs of imperial maintenance. In such manner, particulars tried to rent a contract of exploration of trade, paying an annual sum to the crown, as in the Portuguese trade. Some of these agents also moved along Simon Ruiz’s network. But others were involved in relations with the imperial crowns on a second way, the finance. Maintaining Empires implied a lot of human, technical but also financial means, and most of the times Kings were forced to recur to these merchants, as we will demonstrate. What were the implications of these collaborative relations in both parts? The main goal of this paper is to comprehend the evolution of informal norms within Simon Ruiz’s network and how they influenced cooperative behavior of the agents, particularly analyzing mechanisms of sanctioning, control, punishment and reward, as well as their consequences in different dimensions: future interactions, social repercussions and in agent’s economic health and activity. The research is based in the bills of exchange and commercial correspondence of the private archive of Simon Ruiz, located in the Provincial Archive of Valladollid, Spain.